Automatic 1D integrated geophysical modelling of lithospheric discontinuities: a case study from Carpathian-Pannonian Basin region - GRINČ, Michal; ZEYEN, Hermann; BIELIK, Miroslav (Contributions to Geophysics and Geodesy, 2014)
Using a very fast 1D method of integrated geophysical modelling, we calculated models of the Moho discontinuity and the lithosphere-asthenosphere boundary in the Carpathian-Pannonian Basin region and its surrounding tectonic units. This method is capable to constrain complicated lithospheric structures by using joint interpretation of different geophysical data sets (geoid and topography) at the same time. The Moho depth map shows significant crustal thickness variations. The thickest crust is found underneath the Carpathian arc and its immediate Foredeep. High values are found in the Eastern Carpathians and Vrancea area (44 km). The thickest crust modelled in the Southern Carpathians is 42 km. The Dinarides crust is characterized by thicknesses more than 40 km. In the East European Platform, crust has a thickness of about 34 km. In the Apuseni Mountains, the depth of the Moho is about 36 km. The Pannonian Basin and the Moesian Platform have thinner crust than the surrounding areas. Here the crustal thicknesses are less than 30 km on average. The thinnest crust can be found in the SE part of the Pannonian Basin near the contact with the Southern Carpathians where it is only 26 km. The thickest lithosphere is placed in the East European Platform, Eastern Carpathians and Southern Carpathians. The East European Platform lithosphere thickness is on average more than 120 km. A strip of thicker lithosphere follows the Eastern Carpathians and its Foredeep, where the values reach in average 160 km. A lithosphere thickness minimum can be observed at the southern border of the Southern Carpathians and in the SE part of the Pannonian Basin. Here, it is only 60 km. The extremely low values of lithospheric thickness in this area were not shown before. The Moesian Platform is characterized by an E–W trend of lithospheric thickness decrease.